Performance degradation and process engineering of the 10 kW proton exchange membrane fuel cell stack. (15th March 2021) - Chu, Tiankuo; Zhang, Ruofan; Wang, Yanbo; Ou, Mingyang; Xie, Meng; Shao, Hangyu; Yang, Daijun; Li, Bing; Ming, Pingwen; Zhang, Cunman
Abstract: Insufficient durability of proton exchange membrane fuel cells (PEMFCs) remains one of the important factors hindering their large-scale commercial applications. To investigate the degradation mechanism, we describe the durability test of 10-kW metal plate fuel cell stack containing 30 cells under dynamic driving cycles. After 600 h of testing, the mean voltage decay percentage of the stack under the rated current densities of 1000 mA cm −2 is 2.67%. A semi-empirical model is introduced to predict the remaining useful life of the stack, and the result satisfies the 5000 h target set by the department of energy (DOE). Three cells with the highest, moderate, and lowest rate of decay are disassembled and characterized by electrochemical and physical methods. Scanning electron microscopy (SEM) shows that the cross-section of the cathode catalyst layer (CL) of the 30# MEA has the lowest thickness of 8.45 μm compared with the fresh sample and other samples. Transmission electron microscopy (TEM) shows serious agglomeration of the 30# catalyst. These observations led to serious performance degradation in the 30# cell. The defects in the design of the stack structure leads to the attenuation of the consistency of the stack and further explains stack performance degradation. Highlights: We report durability testing of a 10-kW metal plate fuel cell stack (30-cell) under dynamic driving cycles. A semi-empirical model was introduced to evaluate the remaining useful life of the stack. The degradation mechanism was characterized by electrochemical and physical methods. The main reason for the highest voltage decay of 30# is cathode catalyst degradation.